Anti-Bacterial Effectiveness Test of Basil Leaf Extract (Ocimum basilicum L.) Against Escherichia coli - Halijah, Halijah; Mutiah, Haerul; Syam, Nur Fatiha (Universitas Sembilanbelas November Kolaka, 2021)
Test the Effectiveness of Basil Leaf Extract (Ocimum basilicum L). Against Bacteria Escherichia coli aims to know the ability of basil leaf extract (Ocimum basilicum L).deadly or inhibit escherichia coli bacteria. This research is qualitative experimental research.Basil leaves are extracted using maceration method using entanol solvent 96%. Antibacterial tests are conducted by administering treatment to bacteria with three types of concentrations, namely concentrations of 40%, 60%, 80%, positive control, and negative control.Antibacterial test results of coarse extract of basil leaves (Ocimum basilicum L) have the ability to inhibit escherichia coli bacteria at concentrations of 40%, 60%, and 80% with each halo zone diameter of 1.96 cm, 1.11 cm, 0.89 cm, 1.50 cm, 0.00 cm.Coarse extract of basil leaves (Ocimum basilicum L) has the ability to inhibit bacteria (bacteriostatic) with the most strong halo zone diameter at a concentration of 40 % with a halo zone diameter of 1.96 cm.Â Key word: Effectiveness Test, Ocimum basilicum L., Escherichia coli